2015
DOI: 10.26719/2015.21.6.420
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-linked diabetes in the Arab world: a review

Abstract: The Arab world is experiencing an epidemic of obesity and type 2 diabetes mellitus. This review summarizes the major pathological factors linking obesity to diabetes, focussing on current epidemiological data related to obese diabetic patients in the Arab world, the etiology of the disease and the genetic determinants of diabetes and obesity. There are alarming data related to the rising prevalence of obesity and type 2 diabetes mellitus in children of Arab ethnicity. Replication studies identify several genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Moreover, we observed a higher prevalence of obesity in students of Arab ethnicity compared with other ethnic groups. The main causes of higher obesity in Arab ethnicity may be different dietary habits, inactivity due to the hotter and more humid climate conditions in Khozestan and genetic factors (25). On the other hand, the prevalence of overweight and obesity were lowest in the Sistani and Baluchi ethnic group and a high prevalence of underweight was observed in this group.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, we observed a higher prevalence of obesity in students of Arab ethnicity compared with other ethnic groups. The main causes of higher obesity in Arab ethnicity may be different dietary habits, inactivity due to the hotter and more humid climate conditions in Khozestan and genetic factors (25). On the other hand, the prevalence of overweight and obesity were lowest in the Sistani and Baluchi ethnic group and a high prevalence of underweight was observed in this group.…”
Section: Discussionmentioning
confidence: 97%
“…Obesity is a growing health concern for Kuwait and the Arabian Peninsula . Kuwait is ranked top among the countries that have seen the largest increase in the rate of obesity .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the Asian populations, we found that the genes identified in the Finnish, European, and American populations are mostly related to insulin resistance. The Saudi population is also characterized, as well as many Arab countries, by Adipocyte dysfunction which associates obesity to insulin resistance and diabetes [53]. Research shows that Metformin is the first line treatment for T2D in USA, UK, Finland and Saudi Arabia [5457].…”
Section: Discussionmentioning
confidence: 99%